Combined assessment of high-sensitivity troponin T and noninvasive coronary plaque composition for the prediction of cardiac outcomes - Gitsioudis, Gitsios; Schüssler, Alena; Nagy, Eszter; Maurovich-Horvat, Pál; Buß, Sebastian Johannes; Voß, Andreas; Hosch, Waldemar P.; Hofmann, Nina; Kauczor, Hans-Ulrich; Giannitsis, Evangelos; Katus, Hugo; Korosoglou, Grigorios (Radiology, 2015)
PurposeTo determine the risk-stratification ability of plaque volume and composition assessment with cardiac computed tomographic (CT) angiography and high-sensitivity troponin T (hsTnT) in patients at intermediate risk for coronary artery disease (CAD).Materials and MethodsThe study complied with the Declaration of Helsinki and was approved by the local ethics committee. All patients gave written informed consent. Five hundred twenty-one consecutive patients (mean age ± standard deviation, 62 years ± 10; 256 men and 265 women) were included in this prospective, observational, longitudinal, single-center study. Quantitative cardiac CT angiography analysis was performed in all patients (for 7690 coronary segments), whereas biomarkers (hsTnT and high-sensitivity C-reactive protein) were available in 408 patients (78%). To evaluate the incremental value of cardiac CT angiography and hsTnT for the prediction of cardiovascular events, multivariate Cox regression and integrated discrimination improvement analysis were applied.ResultsIn 521 patients, 13 hard cardiac events occurred during a mean follow-up period of 2.3 years ± 1.1 (median, 2.4 years; range, 0.5-4.5 years), while 23 patients underwent late coronary revascularization. The Duke clinical score was 51% ± 30, indicating intermediate risk. The presence of no plaques or purely calcified versus noncalcified plaques, plaque volume according to tertiles, and increased hsTnT (≥14 pg/mL) was independently associated with hard cardiac events (hazard ratio [HR] = 26.08, 95% confidence interval [CI]: 2.78, 244.99; HR = 12.14, 95% CI: 1.87, 78.74; and HR = 10.31, 95% CI: 2.72, 39.0, respectively; P < .01 for all). Patients with increased hsTnT and plaque burden (n = 53) showed the highest incidence for hard cardiac events (annual rate, 12.7%), followed by those with either increased hsTnT or plaque burden (n = 145; annual rate = 0.44%, P < .03), while those with lower hsTnT and plaque burden exhibited excellent outcomes and no hard event during the follow-up duration (n = 210; annual rate = 0%, P < .001).ConclusionUse of hsTnT as a marker of myocardial microinjury and cardiac CT angiography as a marker of the total atherosclerotic burden improves the prediction of cardiac outcome in patients with presumably stable CAD and may aid in personalized risk stratification in patients at intermediate risk.© RSNA, 2015Online supplemental material is available for this article.